1996
DOI: 10.1128/jb.178.6.1623-1630.1996
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas salmonicida possesses two genes encoding homologs of the major outer membrane protein, OmpA

Abstract: Two homologs of the outer membrane protein OmpA were identified in Aeromonas salmonicida by sodium dodecyl sulfate-polyacrylamide gel electrophoresis, immunoblotting, and amino-terminal sequence analyses. An A. salmonicida genomic DNA library was constructed by using GEM-11 and recombinant phage carrying both genes (ompAI and ompAII) selected by immunoscreening. A 5.0-kb BamHI fragment containing the two genes in tandem was subcloned in pBluescript and used for further subcloning and sequencing of the genes. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
16
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Their tandem arrangement on the chromosome may be due to a gene duplication event. Only one other bacterium, Aeromonas salmonicida, has been reported to express two OmpA-like proteins (8).…”
mentioning
confidence: 99%
“…Their tandem arrangement on the chromosome may be due to a gene duplication event. Only one other bacterium, Aeromonas salmonicida, has been reported to express two OmpA-like proteins (8).…”
mentioning
confidence: 99%
“…on May 7, 2018 by guest http://jb.asm.org/ expected because similar findings have been described for Aeromonas salmonicida and Haemophilus ducreyi (8,29). The presence of putative ribosome-binding, promoter, and termination sequences associated with each of the ompA genes also provides indirect evidence that they are independently transcribed (8,54).…”
mentioning
confidence: 55%
“…It also seems likely that a common underlying mechanism is responsible for generating tandem ompA genes in certain bacterial species and that the expression of two OmpA homologs provides a selective advantage to these organisms. It has been suggested that the two ompA genes of A. salmonicida and H. ducreyi have arisen by gene duplication (8,29). Based on the relatively low level of homology between the two OmpA proteins of A. salmonicida, Costello et al (8) concluded that such a gene duplication event occurred in the distant evolutionary past.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To date, other than the S-layer, a limited number of Aeromonas salmonicida OMPs have been identified. Costello and co-workers reported that A. salmonicida expresses 2 OmpA porin family gene products (OmpAI and OmpAII) coded for by 2 distinct genes (Costello et al 1996). Other A. salmonicida surface proteins identified include a maltose-inducible LamB homolog (Dodsworth et al 1993), the ExeD protein of the general secretion pathway used to translocate extracellular proteins from the periplasmic space across the outer membrane (Karlyshev & MacIntyre 1995), a 43 and a 28 kDa OMP involved in pore-forming activity (Darveau et al 1983, Lutwyche et al 1995.…”
Section: Introductionmentioning
confidence: 99%